Civil engineering aspects of combined cycle gas turbine projects speakers' papers : Thursday 5 November 1992 (Thomas Telford, 1992)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference in conjunction with Institution of Diesel and Gas Turbine Engineers, Institution of Electrical Engineers and the Institute of Energy held on 5 November 1992.